How to understand and use mathematics for derivatives - Chorafas, Dimitris N. (London : Euromoney Books, 1996)
This book brings under one cover all issues regarding trading and investing in foreign exchange and derivatives,together with many studies - plus the hindsight on how risk can be controlled. It also provides a comprehensible explanation of the new terms and techniques in financial analysis: intraday time series, high frequency financial data, heteroschedasticity, microseasonal volatility, intrisic time and business time..
v. 1. Understanding the behaviour of markets -- v. 2. Advanced modelling methods
Includes bibliographical references.
lje 6/9/13, osc 09/09/13
Loans
Keywords: Derivative securities -- Mathematical models; Financial Markets